Prevalence of Enamel Hypoplasia in Neonates with Low Birth Weight and Its Correlation with Early Childhood Caries at One-Year Follow-Up: A Prospective Cohort Study - Ul Ehsan, Hafiz Rabbi; Rana, Nadeem Ahmad; Saqlain, Barzam Ali; Haider Naqvi, Syed Shan E; Rehman, Shafiq Ur; Arif, Marium (Journal of Neonatal Surgery, 2025)
Background: Enamel hypoplasia (EH) is a developmental defect of tooth enamel that results in structural and mineralisation defects, rendering teeth more susceptible to dental caries. Objective: This study aimed to determine the prevalence of enamel hypoplasia in LBW neonates and its correlation with the incidence of ECC at 12 months. Methods: A prospective cohort study was conducted at the Armed Forces Institute of Dentistry (AFID and CMH), Rawalpindi, between January 2023 and July 2025. The study included 390 LBW neonates who were assessed for enamel hypoplasia using the Modified Developmental Defects of Enamel (DDE) Index. The infants were followed up for 12 months to evaluate the development of ECC using the American Academy of Pediatric Dentistry (AAPD) criteria. Results: The prevalence of enamel hypoplasia in LBW neonates was 35.4%, with more severe forms observed in preterm neonates (41.2%). At 12 months, the incidence of ECC was 27.7%, with 62.9% of ECC cases occurring in neonates with enamel hypoplasia. A strong correlation was observed between the severity of enamel hypoplasia and ECC development. Formula feeding (33%) and inadequate oral hygiene practices (32%) were significantly associated with higher ECC incidence. Logistic regression analysis revealed that enamel hypoplasia, formula feeding, and lower socioeconomic status were significant predictors of ECC. Conclusions: The study concludes that enamel hypoplasia is highly prevalent in LBW neonates and significantly contributes to the development of ECC by 12 months of age. Early dental screenings, preventive measures, and parental education on proper oral hygiene practices are essential for reducing the risk of ECC in LBW neonates.